Gabby Garcia's ultimate playbook - Palmer, Iva-Marie (Palmer, Iva-Marie. Gabby Garcia's ultimate playbook, 2017)
When her school is shut down due to an asbestos problem, all-star pitcher Gabby Garcia is sent to an upscale private school that already has a star pitcher, and to make matters worse, she has trouble making friends and finding her place.